Synanthropic Cockroaches (Blattidae: Periplaneta spp.) Harbor Pathogenic Leptospira in Colombia (2016)
Leptospirosis cases in Colombia are typically linked to peridomestic rodents; however, empirical data suggest that Leptospira-infected patients with no apparent exposure to these reservoirs are common. Cockroaches (Periplaneta spp.) have equal or greater interaction with humans than rodents, yet their potential role as carriers of Leptospira has not been assessed. We determined if pathogenic Leptospira is harbored by Periplaneta spp. in Cali (Colombia) and the variables influencing this relationship. Fifty-nine cockroaches were captured from seven sites and DNA was extracted from the body surface and digestive tract for a multiplex polymerase chain reaction, targeting genes secY and flaB. Logistic regression models and proportion tests showed a higher likelihood for Leptospira to be isolated from body surfaces (P>0.001) and from individuals inside houses (six times more likely). These findings are the first to demonstrate an association between Periplaneta spp. and Leptospira, suggesting the need to investigate the potential for cockroaches to serve as reservoirs or transport hosts for Leptospira.